2009
DOI: 10.1371/journal.pone.0007016
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling Of Human Pleural Mesotheliomas: Identification of Matrix Metalloproteinase 14 (MMP-14) as Potential Tumour Target

Abstract: BackgroundThe goal of our study was to molecularly dissect mesothelioma tumour pathways by mean of microarray technologies in order to identify new tumour biomarkers that could be used as early diagnostic markers and possibly as specific molecular therapeutic targets.MethodologyWe performed Affymetrix HGU133A plus 2.0 microarray analysis, containing probes for about 39,000 human transcripts, comparing 9 human pleural mesotheliomas with 4 normal pleural specimens. Stringent statistical feature selection detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 73 publications
0
76
2
Order By: Relevance
“…Survivin overexpression in MPM has been confirmed in different independent cohort of mesothelioma patients (7)(8)(9)11,47,53). Survivin is a multifunctional protein that plays critical roles in several crucial cell processes: several studies described its anti-apoptotic function (49,98,99), a role in microtubule dynamics, in cell proliferation, in cell migration and control bipolar spindle formation (100).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 84%
See 1 more Smart Citation
“…Survivin overexpression in MPM has been confirmed in different independent cohort of mesothelioma patients (7)(8)(9)11,47,53). Survivin is a multifunctional protein that plays critical roles in several crucial cell processes: several studies described its anti-apoptotic function (49,98,99), a role in microtubule dynamics, in cell proliferation, in cell migration and control bipolar spindle formation (100).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 84%
“…In recent years, a number of aberrantly expressed genes were suggested, but with a poor consistency among studies. In 2012, in order to find a consensus among nine independent transcriptome studies carried out between 2000 and 2010 (1)(2)(3)(4)(5)(6)(7)(8)(9), it has been performed a review and a data mining (10) and it has been identified a group of 96 overexpressed genes in MPM compared to non-malignant tissues and cell lines. This group of genes have been further evaluated in 2015 through a gene expression study performed on an independent cohort of mesothelioma tissues compared to non-malignant tissues: the overexpression of 51 genes ( Table 1) have been confirmed (11).…”
Section: Overexpressed Genes Identified In Malignant Pleural Mesothelmentioning
confidence: 99%
“…36 These molecules are able to efflux cytotoxic drugs, affecting the resistance of cancer cells to apoptosis in the context of treatment. However, several reports provide evidence that ABC transporters might also promote cell survival independently of cytotoxic drug efflux, suggesting together with our findings that further experiments are needed to address this issue in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The entire procedure for qRT-PCR analysis-primer design, reactions, amplicon specificity and determination of gene target expression levels-was performed as previously described. 36 Statistical analysis of the c-Myc expression levels were performed using GraphPad Prism 5.0 Ò statistical software (GraphPad Software Inc., La Jolla, CA). Paired t test was used for comparison of 2 paired groups.…”
Section: Real-time Qrt-pcrmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an internal control. The entire procedure for quantitative RT-PCR (qRT-PCR) analysis -including primer design, reactions, amplicon specificity, and determination of gene target expression levels -was performed as previously described (Crispi et al 2009). …”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%